The Effect of Financial Distress, Information Asymmetry, and CEO Characteristics on Earnings Management: The Moderating Role of Internal Control - Nuraeni, Neli; Farida, Ajeng Luthfiyatul (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Even more challenging for companies is keeping their financial statements honest in the face of increasingly complicated rules and intense competition in their respective industries. The temptation for management to resort to earnings management tactics to achieve short-term financial goals can be strong in such a scenario. This research project will look at infrastructure, transportation, and logistics-related IDX-listed firms from 2018 to 2022. It will look for patterns in earnings management as an influence of financial distress, information asymmetry, and CEO characteristics like narcissism and power. We will utilize internal control as a moderator to examine the relationship between earnings management and financial distress. Over the course of 5 years, 59 enterprises were selected via purposive samplingand 295 observations were obtained. For this research, we used panel data regression. The financial distress affected earnings management, but information asymmetry, CEO power, and CEO narcissism had no effect. Internal control may also moderate the association between earnings management and financial distress, according to the findings